Caracterização da silagem pré-secada de capim Tifton 85, com diferentes aditivos e tempos de armazenamento - Nath, Caroline Daiane (2019)
The aim of this study was to evaluate the effect of inclusion of whey powder and bacterial inoculant on the microbiological profile, fermentation, aerobic stability and nutritional value in Tifton 85 bermudagrass haylage with different storage times. For the evaluation of the microbiological profile, fermentative and nutritional value, the experimental design was completely randomized, with four replications, repeated measures in time, three types of haylages (haylages without additive, bacterial inoculant and whey powder) and three storage times (30, 40 and 60 days). For the aerobic stability, the experimental design was completely randomized, with four replications, in a factorial scheme (3 types of haylages x 3 storage times), with measures repeated in time (seven days of exposure to oxygen). The material was ensiled in PVC silos, adapted with Bunsen type valve. Haylage without additive and with bacterial inoculant present higher crude protein content and less effluent loss up to 40 days of storage. The inclusion of whey powder in the haylages increased the total digestible nutrients (6.64%) and the in vitro dry matter digestibility, organic matter and neutral detergent insoluble fiber (9.56, 10.16 and 9.16%, respectively), compared to haylages without additive. Haylages with whey powder stored for a period of 40 days have lower levels of fiber, lignin, neutral detergent insoluble protein and acid and higher recovery of dry matter. The prolongation of the storage time of the haylages reduced the degradable protein fractions in the rumen. Tifton 85 bermudagrass haylages without additive contain less amount of non-protein nitrogen (475.25 g kg- PB) and total carbohydrates (707.89 g kg-1). The storage of the haylages with whey powder until the 40 days provided higher amounts of non-fibrous carbohydrates and smaller indigestible proteins and carbohydrates fractions. Haylage with whey powder stored at 60 days presented a lower population of lactic and clostridial bacteria (6.28 and 7.00 log CFU g, respectively). The use of the inoculant and whey powder didn’t alter the aerobic stability of the haylages at the different storage times evaluated. Tifton 85 bermudagrass haylages without additive and with bacterial inoculant and whey powder present inadequate fermentation profile, with low levels of lactic acid and high concentrations of propionic, butyric acid and pH, during 60 days of storage.